Bacterial cytochrome P450s: a bioinformatics odyssey of substrate discovery - Schottlender, Gustavo; Prieto, Juan Manuel; Clemente, Camila; Schuster, Claudio David; Dumas, Victoria; Fernández Do Porto, Darío; Martí, Marcelo Adrian (Frontiers in Microbiology, 2024)
Bacterial P450 cytochromes (BacCYPs) are versatile heme-containing proteins responsible for oxidation reactions on a wide range of substrates, often contributing to the production of valuable natural products with biotechnological potential. While the sequencing of microbial genomes has provided a wealth of BacCYP sequences, functional characterization lags behind, hindering our understanding of their roles. This study employs a comprehensive approach to predict BacCYP substrate specificity, bridging the gap between sequence and function. The research begins with an in-depth analysis of BacCYP sequence diversity and structural characteristics, revealing conserved motifs and recurrent residues in the active site. Phylogenetic analysis identifies distinct groups within the BacCYP family based on sequence similarity. However, our study reveals that sequence alone does not consistently predict substrate specificity, necessitating additional approaches. The study delves into the genetic context of BacCYPs, utilizing neighboring gene information to infer potential substrates. This approach proves effective in many cases. Molecular docking is employed to assess BacCYP-substrate interactions, confirming the potential substrates and providing insights into selectivity. Finally, a comprehensive strategy is proposed for predicting BacCYP substrates, involving sequence analysis, structure modeling, genetic context, and docking. The 1 effectiveness of this strategy is demonstrated with two case studies, highlighting its potential for substrate discovery.